Cover Feature: Hierarchical Self‐Assembly of Supramolecular Coordination Polymers Using Giant Metal–Organic Nanocapsules as Building Blocks (Chem. Eur. J. 54/2018). Issue 54 (16th September 2018) - Zhang, Chen; Wang, Fang; Patil, Rahul S.; Barnes, Charles L.; Li, Tao; Atwood, Jerry L.
Abstract : Self‐assembly of giant molecular nanocapsules into supramolecular coordination polymers (SCPs) with controlled hierarchy by analogy with protein assembly is presented here. First, discrete nanocapsules (secondary structures) are prepared which consist of multicomponents such as organic macrocycles and metal‐based secondary building units (primary structures). Second, these nanocapsules can self‐organize into various 2D and 3D SCPs (tertiary structures) by coordination‐driven assembly. More information can be found in the Communication by T. Li, J. L. Atwood et al. onpage 14335 .